1983
DOI: 10.1007/bf00443036
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided manufacture of individual endoprostheses

Abstract: Long-term anchorage of foreign material in vital bone has proven to be the main problem in endoprosthetics. In the authors' opinion, modelling an endoprosthetic anchorage component to the individual anatomic needs is, at present, the best way to transmit stresses harmoniously from the prosthesis to the sensitive bone, in order to utilize functional adaptation, and to guarantee long-term function. The production of a true-to-scale joint model is possible with computer-assisted tomography. This model of the join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Because of the large anatomical variation in the femoral geometry at different locations, close-fitting femoral components cannot be consistently achieved with standard commercially available implants (Wettstein et al 2005). In order to solve this geometrical mismatch between the femoral canal and uncemented implants, custom-made femoral stems were initially developed in the 1980s (Aldinger et al 1983) and refined in the 1990s as computer technology became more widely used (Aamodt et al 2001). Here we report on a series of 3-dimensionally computed custom stems in a subgroup of high-risk patients (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the large anatomical variation in the femoral geometry at different locations, close-fitting femoral components cannot be consistently achieved with standard commercially available implants (Wettstein et al 2005). In order to solve this geometrical mismatch between the femoral canal and uncemented implants, custom-made femoral stems were initially developed in the 1980s (Aldinger et al 1983) and refined in the 1990s as computer technology became more widely used (Aamodt et al 2001). Here we report on a series of 3-dimensionally computed custom stems in a subgroup of high-risk patients (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…7 Since we introduced this stem in our clinic it has been combined with the HarrisGalante I cup. In 48 hips, other stems were used.…”
Section: Methodsmentioning
confidence: 99%
“…The femoral components of conventional total hip endoprostheses are usually available in standardized shapes in various sizes to offer surgeons the opportunity to select the best fitting size. More recently, custom femoral components have been designed, based on the concept don't fit the bone to the prosthesis, but the prosthesis to the bone (Aldinger, 1983), 1 but there is controversy about the relative benefits of custom prostheses. It had been suggested that a high percentage of cortical form-fit of custom implants may decrease the frequency of aseptic loosening and improve long-term stability; however, bone density studies (postoperative follow-up, 5 years) have shown that a custom femoral component (evolution hip endoprosthesis) may not prevent a reduction in periprosthetic bone density and stress shielding, despite a high form-fit.…”
Section: Introductionmentioning
confidence: 99%